-5(x+1)-12=15+3

Simple and best practice solution for -5(x+1)-12=15+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+1)-12=15+3 equation:


Simplifying
-5(x + 1) + -12 = 15 + 3

Reorder the terms:
-5(1 + x) + -12 = 15 + 3
(1 * -5 + x * -5) + -12 = 15 + 3
(-5 + -5x) + -12 = 15 + 3

Reorder the terms:
-5 + -12 + -5x = 15 + 3

Combine like terms: -5 + -12 = -17
-17 + -5x = 15 + 3

Combine like terms: 15 + 3 = 18
-17 + -5x = 18

Solving
-17 + -5x = 18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + -5x = 18 + 17

Combine like terms: -17 + 17 = 0
0 + -5x = 18 + 17
-5x = 18 + 17

Combine like terms: 18 + 17 = 35
-5x = 35

Divide each side by '-5'.
x = -7

Simplifying
x = -7

See similar equations:

| 6(3x-4)+5=-11x+13+12w | | 3x-63+x+37=180 | | -2x+x+2(-1x+2)=x | | 7=-11+3(n+5) | | 7(n+1)=2(3-n) | | 9a^2-12a=0 | | -2x+2x+x+2(-1x+2)=x | | 8-(x+2)=12 | | 7x-(2+7)=28 | | t-17l=5 | | 2x+2(x+4)=3x+14 | | 0.43*0.71= | | Y=-6x-16 | | log(13)*(-4x-1)=log(13)*(2x+5) | | 2x-16+2x+1+x=180 | | 6(3x-4)+5=-11x+14+12w | | N+7=3n-5 | | x^4+-26x^2+160=0 | | -6=x+20 | | 28=-7 | | .4m+6.4=4.9 | | 21x+1=21x+36x+5 | | 4b=2.8 | | 2(a-10)-8=2 | | -1(2r-7)=-2(r-8) | | 6(x+4)+8=8x-2(x-4) | | x^4+15x^2+62=0 | | -2(3s-1)-2=-3(4s+3)-3 | | x^2+4x-428=0 | | 72=5v+12 | | 10-5(x+4)=31 | | -63=-7y |

Equations solver categories